PERILAKU INSES PADA GRUP FACEBOOK “FANTASI SEDARAH”: ANALISIS DISFUNGSI KELUARGA DI INDONESIA (PENDEKATAN FENOMENOLOGIS) - Fajar Apriani; Pipit Afrianti; Diah Rahayu (Universitas Negeri Medan, 2025)
Incest is a serious form of sexual violence within the family because it occurs in the home, where the victim and the perpetrator live together, placing the victim in a powerless position when facing a family member. This study aims to examine the impact of incest as a sexual crime on victims and its effects on family functioning. This research uses a qualitative method with a phenomenological approach and focuses on the online phenomenon of the Facebook group ‘Fantasi Sedarah’ (Incest Fantasy). Data were collected through document analysis of secondary sources, including media reports, publications from organizations working on the protection of women and children, and academic studies on sexual violence within families. The analysis combines perspectives from feminism, family sociology, psychology, and child and family social welfare. The findings show that perpetrators view victims as sexual objects and develop distorted sexual perceptions, which damage their role and responsibilities as parents. Incest leads to the breakdown of family relationships, weakens protective functions, and has wider negative social impacts. This study highlights that Indonesia’s response to incest cases remains limited, particularly in linking legal processes with victim-centered social support. So, stronger structural and cultural actions by the government are urgently needed to restore family functioning, ensure justice, and protect women and children from sexual violence